Pancoast’s Syndrome due to Fungal Abscess in the Apex of Lung in an Immunocompetent Individual: A Case Report and Review of the Literature - Anirban Das; Sabyasachi Choudhury; Sumitra Basuthakur; Sibes Kumar Das; Angshuman Mukhopadhyay (Case Reports in Pulmonology)
Malignant tumours in the apices of the lungs, especially bronchogenic carcinoma (Pancoast tumours), are the most common cause of Pancoast’ syndrome which presents with shoulder or arm pain radiating along the medial aspect of forearm and weakness of small muscles of hand with wasting of hypothenar eminence due to neoplastic involvement of C8 and T1 and T2 nerve roots of brachial plexus. There are a number of benign conditions which may lead to Pancoast’s syndrome; fungal abscess located in the apex of lung is one of them. Oral or intravenous antifungals are the treatment of choice in this case and complete recovery is usual, whereas, surgical resection followed by chemoradiotherapy is the treatment of choice in case of Pancoast’s syndrome due to lung cancers. Hence, tissue diagnosis is mandatory. Here, we report a case of apical fungal abscess causing Pancoast’s syndrome in an immunocompetent individual of 35 years of age to raise the awareness among the clinicians regarding this rare clinical entity.